2012
DOI: 10.1371/journal.pone.0029213
|View full text |Cite
|
Sign up to set email alerts
|

Small Interfering RNA Targeted to IGF-IR Delays Tumor Growth and Induces Proinflammatory Cytokines in a Mouse Breast Cancer Model

Abstract: Insulin-like growth factor I (IGF-I) and its type I receptor (IGF-IR) play significant roles in tumorigenesis and in immune response. Here, we wanted to know whether an RNA interference approach targeted to IGF-IR could be used for specific antitumor immunostimulation in a breast cancer model. For that, we evaluated short interfering RNA (siRNAs) for inhibition of in vivo tumor growth and immunological stimulation in immunocompetent mice. We designed 2′-O-methyl-modified siRNAs to inhibit expression of IGF-IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 66 publications
(103 reference statements)
1
24
0
Order By: Relevance
“…Durfort et al . reported that knockdown of IGF-1R increased the infiltration of lymphocytes and polymorphonuclear neutrophils, and induced secretion of two pro-inflammatory cytokines, TNF-α and IFN-γ 23 . Therefore, we hypothesized that citrate treatment may suppress tumor growth via inhibition of IGF-1R phosphorylation (and activity), which might increase tumor-infiltrating T lymphocytes and pro-inflammatory cytokines.
Figure 5Citrate treatment impacts IGF-1R-AKT pathway.
…”
Section: Resultsmentioning
confidence: 97%
“…Durfort et al . reported that knockdown of IGF-1R increased the infiltration of lymphocytes and polymorphonuclear neutrophils, and induced secretion of two pro-inflammatory cytokines, TNF-α and IFN-γ 23 . Therefore, we hypothesized that citrate treatment may suppress tumor growth via inhibition of IGF-1R phosphorylation (and activity), which might increase tumor-infiltrating T lymphocytes and pro-inflammatory cytokines.
Figure 5Citrate treatment impacts IGF-1R-AKT pathway.
…”
Section: Resultsmentioning
confidence: 97%
“…The compound reportedly possesses both signal inhibitory properties and downregulates IGF-IR in vitro [51]. A phase I trial of this drug has been completed showing favorable safety and pharmacokinetics profiles of PPP in patients with advanced cancer (NCT01062620).…”
Section: Strategies In Targeting the Igf-i/insulin Systemmentioning
confidence: 99%
“…Recently, an interesting preclinical study showed that 2’-O-methyl modified IGF-IR specific siRNA are able to downregulate IGF-IR expression, block IGF-IR signaling, and suppress tumor growth in vivo by triggering antitumor immune responses [51]. siRNA-based therapies face two major barriers: the delivery of the large and highly charged molecules to the targets [52] and the transient effects of the downregulation of the target gene.…”
Section: Strategies In Targeting the Igf-i/insulin Systemmentioning
confidence: 99%
“…The current study is the first, to our knowledge, to show that reduction in circulating IGF1 levels (either genetically or by CR), despite elevated circulating levels of insulin, decreases ERa low luminal mammary tumor growth. We also demonstrate in the Met1 ERa low luminal B breast cancer model that, despite enhanced serum insulin levels, reduced circulating levels of IGF1 decrease Akt signaling (pAkt and cyclin D1) and EMT and chemokine gene expression, all of which regulate tumor growth, progression, and/or metastatic potential in other cancer models (Ahmad et al 1999, Mira et al 1999, 2001, Akekawatchai et al 2005, Singh et al 2009, Wu et al 2010, Durfort et al 2012. Pharmacological inhibitors of the IGF1 pathway effectively diminish breast tumor growth in several preclinical models of breast cancer (Maloney et al 2003, Haluska et al 2006, Gualberto & Pollak 2009, Sabbatini et al 2009, Sun et al 2011.…”
Section: Discussionmentioning
confidence: 65%